LGG-45. A REPORT OF IDH-MUTANT BRAINSTEM ASTROCYTOMAS IN YOUNG ADULTS. (4th December 2020) - Chang, Ellen; Tamrazi, Benita; Cotter, Jennifer; Margol, Ashley
Abstract: IDH-mutant astrocytomas are well-recognized in the adult population and while increasingly identified, are rare in children and young adults. These tumors typically arise in cortical locations, however cases of these tumors occurring in the brainstem have been reported in the adult literature. Here we present two cases of young adults with IDH-mutant astrocytomas of the brainstem. Patient 1 was initially diagnosed with an infiltrative low grade glioma (LGG) of the brainstem at 19 years of age based on conventional magnetic resonance imaging and magnetic resonance spectroscopy characteristics. She was treated with LGG therapy and had stable disease for over three years. At the time of disease progression she underwent biopsy and pathology was consistent with an anaplastic astrocytoma, IDH1 R132S mutant. Despite treatment she experienced rapid disease progression and died six months later. Patient 2 is a 17-year-old male who underwent up-front biopsy of an infiltrating brainstem lesion; pathology was consistent with diffuse astrocytoma, IDH1 R132H mutant. He was treated with focal irradiation and chemotherapy and continues to have stable disease 26 months post diagnosis. To our knowledge, this is the first report of IDH-mutant astrocytomas occurring the brainstem in young adult patients. Both patients' tumors harbored accompanying TP53 mutations, but not ATRX mutations. These two cases reveal the importance of obtaining biopsies for brainstem tumors to perform molecular characterization and appropriate prognostication.